1996
DOI: 10.1111/1523-1747.ep12327815
|View full text |Cite
|
Sign up to set email alerts
|

Production of Interleukin-6 by Human Mast Cells and Basophilic Cells

Abstract: Since mast cells and basophils are thought to play a central role in several types of cutaneous inflammatory and allergic reactions, and since interleukin-6 (IL-6) is an important mediator in these processes, we have studied the ability of the human mast cell line HMC-1, the human basophilic cell line KU812, and human skin mast cells to produce IL-6. All three cell types proved to be potent sources of this cytokine after appropriate stimulation. Transcription of IL-6 mRNA was first detectable 2 h after stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 30 publications
4
55
1
2
Order By: Relevance
“…By immunohistochemistry, mast cells of the MC TC phenotype in skin as well as ocular and respiratory tissues appeared to contain IL-4 and IL-13, but little if any IL-5 and IL-6, whereas MC T cells contained IL-5 and IL-6 and lesser levels of IL-4 (9,10). In contrast, another study of human skin-derived mast cells showed IL-6 mRNA and protein production after stimulation (11). Skin-derived mast cells also produce IL-8 (12) and TNF-␣ (13); however, in this latter study, no IL-4, IL-5, or IL-13 was detected.…”
contrasting
confidence: 70%
“…By immunohistochemistry, mast cells of the MC TC phenotype in skin as well as ocular and respiratory tissues appeared to contain IL-4 and IL-13, but little if any IL-5 and IL-6, whereas MC T cells contained IL-5 and IL-6 and lesser levels of IL-4 (9,10). In contrast, another study of human skin-derived mast cells showed IL-6 mRNA and protein production after stimulation (11). Skin-derived mast cells also produce IL-8 (12) and TNF-␣ (13); however, in this latter study, no IL-4, IL-5, or IL-13 was detected.…”
contrasting
confidence: 70%
“…LPS (50 g/ml) was used as additional stimulus but did not result in a significant release of IL-4. These functional properties were very much reminiscent of the previously described IL-4-secreting non-B non-T cells (19) and raised the possibility that the cell population might consist of basophilic granulocytes that are know to release IL-4 after stimulation (20,21). Indeed, staining with Abs against IgE and the IL-3R (CD123) showed that all allophycocyanin-positive non-B cells were highly positive for both molecules (Fig.…”
Section: Detection and Characterization Of Ag-capturing Cellssupporting
confidence: 56%
“…In addition, IL-4-positive mast cells are signiWcantly associated with the size of allergic skin prick-test wheal reaction and serum total IgE levels [156]. Even though human mast cells have been shown to express IL-6 and TGF-1 [88,99]; it is, however, not known to what extent mast cells contain these Th17 priming cytokines in the psoriatic skin. Our preliminary results suggest that mast cells contain IL-6 immunoreactivity in the developing psoriatic lesion induced by the tape-stripping technique (Suttle et al, unpublished results) (Fig.…”
Section: Mast Cells In Relation To Cells Of the Immune System In Psormentioning
confidence: 99%